2001
DOI: 10.1007/s001250051614
|View full text |Cite
|
Sign up to set email alerts
|

The role of viruses in Type I diabetes: two distinct cellular and molecular pathogenic mechanisms of virus-induced diabetes in animals

Abstract: Type I (insulin-dependent) diabetes mellitus results from the progressive destruction of insulin-producing pancreatic beta cells, which leads to the development of hypoinsulinaemia and hyperglycaemia [1±8]. It is believed that genetic factors are a major component in the aetiology of Type I diabetes because a strong association has been observed between susceptibility to Type I diabetes and specific alleles of the MHC class II genes [9±17]. Although genetic susceptibility seems to be a prerequisite, studies on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
89
0
6

Year Published

2001
2001
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(99 citation statements)
references
References 41 publications
3
89
0
6
Order By: Relevance
“…Another recent study has observed the presence of CXCL10 and infiltration of lymphocytes expressing the corresponding chemokine receptor CXCR3 in islets from pancreatic tissues of deceased recent-onset type 1 diabetic patients, regardless of enterovirus infection; this suggests a significant role for this chemokine in inducing insulitis [17]. Viral infection can also cause direct injury to beta cells [39]. Coxsackievirus-induced beta cell death in cultured human islets has been reported [40].…”
Section: Discussionmentioning
confidence: 97%
“…Another recent study has observed the presence of CXCL10 and infiltration of lymphocytes expressing the corresponding chemokine receptor CXCR3 in islets from pancreatic tissues of deceased recent-onset type 1 diabetic patients, regardless of enterovirus infection; this suggests a significant role for this chemokine in inducing insulitis [17]. Viral infection can also cause direct injury to beta cells [39]. Coxsackievirus-induced beta cell death in cultured human islets has been reported [40].…”
Section: Discussionmentioning
confidence: 97%
“…In a rodent model, it has been suggested that viruses are involved in the pathogenesis of Type 1 diabetes in at least two distinct ways: (i) by inducing beta-cellspecific autoimmunity; and (ii) by inducing cytolytic infection leading to the destruction of the beta cells [24]. The infection of genetically susceptible strains of mice with a high titre of EMC-D (D variant of the encephalomyocarditis) results in the rapid onset of diabetes within 3 days, largely due to the replication of the virus within beta cells.…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, 13 different viruses, most of them belonging to the enterovirus family, have been found to be associated with the onset of Type 1 Diabetes in humans and in various animal models [7]. Different mechanisms have been proposed for the role of viruses in the pathogenesis of Type 1 Diabetes.…”
mentioning
confidence: 99%
“…GADD65) and a viral antigen, leading to autoimmune destruction of the beta cell [11]; (iv) viral infection, coupled with one or more of the factors described above, acting in conjunction to induce beta cell death [12]. For example, mouse infection with a high titre of the D variant of the encephalomyocarditis (EMC-D) virus leads to beta-cell destruction and diabetes mainly as a result of viral replication within beta cells, while mouse infection with a low titre of EMC-D virus leads to diabetes as a chronic process, caused by the destruction of beta cells by soluble mediators such as IL-1β, TNF-α/β and NO produced by macrophages or the beta cells themselves [7].…”
mentioning
confidence: 99%